PENGEMBANGAN MODEL PETA PIKIRAN (MIND MAPPING) BERBASIS NILAI PROFETIK DALAM PEMBELAJARAN MENULIS EKSPOSISI SISWA KELAS X SMA DI KABUPATEN BANDUNG - Neneng Maelasari, - (2021)
ABSTRAK Penelitian ini dirancang untuk mengembangkan dan menguji efektivitas model peta pikiran berbasis nilai profetik (Model 2P-BNP) dalam pembelajaran menulis eksposisi siswa kelas X SMA di Kabupaten Bandung. Rumusan penelitian ini adalah sebagai berikut. Bagaimanakah 1) profil pembelajaran menulis eksposisi siswa kelas X SMA di Kabupaten Bandung? 2) model hipotetik 2P-BNP dalam pembelajaran menulis eksposisi? 3) pengembangan model 2P-BNP dalam pembelajaran menulis eksposisi? 4) respons pengguna terhadap model 2P-BNP dalam pembelajaran menulis eksposisi? 5) produk akhir model 2P-BNP dalam pembelajaran menulis eksposisi? Metode penelitian ini menggunakan Research and Development dengan pengembangan suatu model peta pikiran konvensional dan mengintegrasikan dengan nilai profetik dalam pembelajaran menulis eksposisi. Pendekatan penelitian ini diambil dari Thiagarajan, D. Semmel, M. Semmel (1974) yakni four D models (Define, Design, Develop, and Disseminate). Instrumen penelitian yang digunakan adalah instrumen tes dan nontes. Hasil penelitian ini diawali dengan uji coba terbatas dilanjutkan dengan melakukan uji coba meluas. Kinerja menulis siswa sebelum dan sesudah diberikan perlakuan dengan model peta pikiran berbasis nilai profetik tampak perbedaan yang signifikan. Hal tersebut terlihat dari hasil pengolahan data saat dilakukan uji coba terbatas memperoleh nilai rerata paired sample test 18,388 dilanjutkan uji coba meluas memperoleh nilai rerata paired sample test -16, 639 dan -17,141. Secara umum, diketahui bahwa kenaikan nilai hasil pascates pada ketiga kelas adalah signifikan. Dengan demikian, model pembelajaran ini terbukti dapat meningkatkan kemampuan siswa dalam menulis eksposisi. Produk akhir dari penelitian ini adalah desain produk model 2P-BNP, sintaks produk model 2P-BNP, dan skema produk model 2P-BNP dalam pembelajaran menulis eksposisi siswa kelas X SMA di Kabupaten Bandung. Kata Kunci: Model Peta Pikiran, Nilai Profetik, Pembelajaran Menulis Eksposisi ABSTRACT This study was designed to develop and test the effectiveness of the prophetic value-based mind map model (2P-BNP) in writing exposition learning of the first grade students of senior high schools in Bandung Regency. Research formulation this study is to How: 1) the profile of learning exposition writing of the first grade students of senior high schools in Bandung Regency?; 2) a hypothetical model of mind mapping based on prophetic value in learning exposition writing?; 3) the development of mind mapping model based on a prophetic value in writing exposition learning?; 4) the response of the first grade of senior high school students toward mind mapping model based on prophetic value in writing exposition learning?; 5) the final product of the mind map model prophetic value-based in the learning to write exposition in the first grade students of senior high school in Bandung Regency? This research method was designed by applying Research and Development (R&D) with the development of a conventional mind map learning model and integrating it with prophetic values. The approach of this research is from Thiagarajan, D. Semmel. M. Semmel (1974, in Sugiyono, 2015. p. 37) who explains that the research and development procedure is through four steps, namely abbreviated as 4 D, which stands for Define, Design, Develop and disseminate. The research instruments used were a test and non-test instrument. The results of this study were preceded by a limited trial to the first grade students of SMAN 1 Baleendah, and it was continued to extensive testing on students of the first grade of SMAN 1 Soreang in Bandung Regency. The writing performance of students before and after being given treatment with a prophetic value-based mind mapping learning model showed a significant difference between schools. This can be seen from the results of data processing when the limited test was carried out, the mean value of paired sample test was 18,388 (First grade of IPA 1 students of SMAN I Baleendah), continued to the extended test to obtain a mean value of paired sample test -16, 639 (first grade students of IPA 3) and -17,141 (first grade students of IPS 5) SMAN I Soreang. In general, it is known that the increase in post-test scores for the three classes is significant. Thus, this learning model is proven to be able to improve students' ability in writing exposition. The final products of this study are: the design 2P-BNP product model, the 2P-BNP product syntax, and the 2P-BNP product scheme in to write exposition learning at the first grade students of senior high schools in Bandung Regency. Keywords: Mind Mapping Model, Prophetic Value, Exposition Writing Learning